Relations Among Maternal Life Satisfaction, Shared Activities, and Child Well-Being - Richter, Nina; Bondü, Rebecca; Spiess, C. Katharina; Wagner, Gert G.; Trommsdorff, Gisela (Frontiers in Psychology, 2018)
Maternal well-being is assumed to be associated with well-being of individual family members, optimal parenting practices, and positive developmental outcomes for children. The objective of this study was to examine the interplay between maternal well-being, parent-child activities, and the well-being of 5 to 7-year old children. In a sample of N = 291 mother-child dyads, maternal life satisfaction, the frequency of shared parent-child activities, as well as children’s self-regulation, prosocial behavior, and receptive vocabulary were assessed using several methods. Data were collected in a special study of the Socio-Economic Panel study (SOEP), a representative longitudinal survey of private households in Germany. Using structural equation modeling, significant positive direct and indirect relations between maternal life satisfaction, frequency of shared parent-child activities, children’s self-regulation, prosocial behavior, and receptive vocabulary were found. The more satisfied the mother was, the more she shared activities with her child and the more the child acted prosocially. Furthermore, the higher the frequency of shared parent-child activities, the higher the child scored in all three analyzed indicators of children´s well-being: self-regulation, prosocial behavior, and receptive vocabulary. The current study supports the assumption of maternal well-being as the basis of positive parenting practices and child well-being.